THE DEVELOPMENT OF STUDENT MISCONCEPTIONS DETECTION AND REDUCTION SOFTWARE IN REACTION RATE MATERIAL WITH CONCEPTUAL CHANGE TEXT STRATEGY (UNESA Journal of Chemical Education, 2019)
This Study aimed to get a feasible software in detect and reduce students’ misconceptions on reaction rate topic. This feasibility was viewed from the validity, practicality, and effectiveness of the software. Method of the research used research and development (R&D). The subjects in the research were 12 students of XI MIPA in SMAN Jogoroto, who had receive the reaction rate material. The method which is used to detect students misconceptions is a three-tier test, while the strategy used to reduce misconceptions is conceptual change text strategy. Based on the results of validation by 3 validators, the content validity of the software was 89.92% in very valid category, while the construct software validity in linguistic, presentation, graphic, and software requirements as ICT media criteria be successive were 81.67%, 85.56%, 87.33%, and 82.22%, so four criteria for construct validity of software can be categorized as very valid. The practicality of software based on the response questionnaire supported by the student activity observation were 95.16% and 91% in very practical categories. Based on shifting students conceptions from misconceptions to know concepts in preliminary field testing, the effectiveness of software was 82.13% in very effective category. This shows that the software fulfills 3 feasibility criteria, so the software is appropriate used to detect and reduce students’ misconceptions in the reaction rate material, that is the effect of surface area, catalyst, temperature, and concentration on the reaction rate concept. Keywords: Software, misconception, reaction rate, conceptual change text.